Forty years after the promise of «ceramic steel?»: Zirconia‐based composites with a metal‐like mechanical behavior. Issue 3 (18th December 2019) - Chevalier, Jérôme; Liens, Aléthéa; Reveron, Helen; Zhang, Fei; Reynaud, Pascal; Douillard, Thierry; Preiss, Laura; Sergo, Valter; Lughi, Vanni; Swain, Mike; Courtois, Nicolas
Abstract: Forty years ago, Garvie and his Australian co‐workers reported that the stress‐induced transformation of metastable tetragonal zirconia grains to the monoclinic symmetry could give rise to a powerful toughening mechanism. Their results even led them to consider zirconia systems as analogues of certain steels. This seminal paper generated extraordinary excitement in the ceramic community and it is still the subject of extensive research. Transformation toughening is widely used in zirconia materials and results in an increase in strength and toughness when compared to nontransformable ceramics, but the implementation into strong, tough, and sufficiently stable materials has not been fully reached. Zirconia ceramics generally fail at low strains with a much larger scatter in the strength values than metals and require statistical approaches to failure. Here we describe in detail the mechanical behavior laws of ceria‐doped zirconia composites exhibiting a high degree of stress‐induced transformation. They present, to some extent, mechanical behavior analogous to a metal, displaying, (a) significant amount of transformation‐induced plasticity without damage, (b) very high flaw tolerance and (c) almost no dispersion in strength data. They potentially open new application avenues in situations where the advantages of ceramics were dampened by their brittle failure behavior. In particular, the consequences of such behavior for dental implants and additive‐manufactured structures are highlighted. Abstract : Stress‐strain curve of the Ce‐TZP composite, showing plasticity before failure even in the presence of a large defect (left). This kind of composites is quite similar to cast iron and other metallic alloys in terms of defect tolerance and mechanical behavior (right).